Quality Assessment of community pharmacy services provided in the United Arab Emirates: patient experience and satisfaction - Farah K. Alhomoud,Amr Kunbus,Ahmed Ameer,Faten Alhomoud (Journal of Applied Pharmaceutical Science, 2016)
Whilst a limited number of studies have been conducted in nearby Arab countries to evaluate patients’ experiences and satisfaction with community pharmacy services provided, in the UAE, this area remains unexamined. Therefore, this study assessed patients’ experiences and satisfaction with community pharmacy services in the UAE, which can be used as an indicator to improve services. An online questionnaire was distributed through social media platforms to customers accessing community pharmacies and who are living in the UAE. The study showed that patient satisfaction regarding the two areas, which includes items on communication quality and other aspects of service delivery quality, was more than the average of Likert scale (cut point=3). However, items on satisfaction with consultation quality were a little less than the mentioned cut point. The worst experience, the one with the lowest level of satisfaction, was associated with non-Arabic or non-English speakers and participants over 60 years. The community pharmacy services provided in the UAE are seen to be traditional or product-focused with minimal or negligible pharmaceutical care provided. Therefore, unique structure strategies and health system reforms need to be introduced to follow the trend of extending community pharmacists’ roles and to meet the growing needs of patients.
Keywords: Patient satisfaction,patient experience,community pharmacy services,United Arab Emirates.